Conjunctival squamous cell carcinoma: Prognostic factors for the recurrence and metastasis and clinicopathological characteristics at an oncological hospital in Peru - Cruzado-Sanchez, Deivy (2020)
Background/aims Conjunctival squamous cell carcinoma (CSCC) is the most frequent malignant tumour of the conjunctiva, with scarce recurrence and infrequent metastasis. The purpose of this study is to describe the clinical and pathological characteristics of this neoplasm and to identify the prognostic factors for recurrence and metastasis in a cancer hospital in Peru. Materials and method A longitudinal, retrospective study of 176 consecutive patients diagnosed with SCC of the conjunctiva. Sociodemographic and clinical characteristics were evaluated. In addition, Kaplan-Meier curves were performed, and Cox regression was used to determine prognostic factors for recurrence and metastasis over time. Result Only 12.5% presented tumour size ≤5 mm. The highest proportion according to the histopathological type was the well-differentiated infiltrative forms (40.9%), and according to tumour, node, metastases (TNM), stage T3 was the most frequent (31.3%). The most performed initial treatment was orbital exenteration (38.6%). The proportion of recurrence was 6.8% and 8.0% for metastasis. The annual survival rate was 7% and the annual metastasis rate was 6%; for recurrence after 5 years, the survival rate was 11% and the metastasis rate was 14%. No prognostic factor evaluated was significant. Conclusion This is the most extensive patient study in Latin America with CSCC, with a high proportion of advanced histopathological grade, TNM stages, and radical treatments such as exenteration. Recurrence rates on average are similar to other reported studies, and it describes the rates of metastasis that have been poorly described in the literature.